A new species of Litoria (Anura: Hylidae) with a highly distinctive tadpole from the north-western Kimberley region of Western Australia - Anstis, Marion; Tyler, Michael J.; Roberts, J. Dale; Price, Luke C.; Doughty, Paul (Zootaxa, 2010)
We describe a small hylid frog species with a highly distinctive tadpole from the Kimberley region of northern Western Australia. The new taxon is morphologically very similar to Litoria meiriana but can be differentiated using a combination of adult and larval morphology and male calls. Tadpoles of the new taxon can be readily differentiated from those of L. meiriana by their unique black, gold and red pigment patterns and the continuous papillary border around the oral disc. Advertisement calls of L. aurifera sp. nov. are longer, have more pulses, have more marked frequency modulation and are produced at a lower rate than those of L. meiriana. Litoria aurifera sp. nov. is only known from locations up to about 100 km south of the Prince Regent River and is associated with small creeks on massive sandstone escarpments, while L. meiriana is widespread in escarpments across northern Western Australia and the northern part of the Northern Territory.